2014
DOI: 10.2146/ajhp130686
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a hospitalwide pharmacy practice model change on readmission and return to emergency department rates

Abstract: Implementation of a team-based pharmacy practice model resulted in a significant decrease in the rate of 30-day readmissions for high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
80
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 16 publications
1
80
0
Order By: Relevance
“…A recently published article in the American Journal of Health-System Pharmacy describes the effects of a hospital-wide pharmacy practice model change on readmission rates at an academic medical center [7].…”
Section: Pharmacist Integration Into Transitions Of Care At a Communimentioning
confidence: 99%
“…A recently published article in the American Journal of Health-System Pharmacy describes the effects of a hospital-wide pharmacy practice model change on readmission rates at an academic medical center [7].…”
Section: Pharmacist Integration Into Transitions Of Care At a Communimentioning
confidence: 99%
“…Transitions of care can contribute to occurrences of medication discrepancy . Pharmacists' interventions during transitions of care, such as medication reconciliation or counselling, reduce medication errors and improve clinical outcomes . Previous research has demonstrated that pharmacist‐led discharge counselling improves medication adherence and reduces medication errors, readmission rates, emergency department visits, and mortality, and consequently, promotes health care cost savings .…”
Section: Introductionmentioning
confidence: 99%
“…Implementation of a pharmacist‐driven TOC process has been shown to reduce rates of medication errors and readmissions and has increased adherence and understanding of medications in patient populations including those with heart failure, chronic obstructive pulmonary disease (COPD), and those with high‐risk medication use . There is a wealth of data showing a reduction in readmission rates in heart failure patients with pharmacy TOC programs.…”
Section: Introductionmentioning
confidence: 99%